2013
DOI: 10.1007/s00403-013-1353-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the pro-inflammatory cytokines and matrix metalloproteinases production in co-cultivated human keratinocytes and melanocytes

Abstract: The human epidermis exerts immunoregulatory functions through the variety of cytokines and other molecules elaborated by keratinocytes and melanocytes. Their constitutive production is very low; however, considerably increased upon stimulation. In vivo, keratinocytes and melanocytes have a typical exposure in the skin, referred as melanocyte epidermal unit. In the present study we co-cultivated these cells in vitro proposing to elucidate some communication links in close cell-to-cell association. We assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…1). 3,[6][7][8] Furthermore, several studies have shown that extracellular matrix (ECM) proteins, which are responsible for structure formation and the transduction of cellular signalling pathways in the skin, can affect melanogenesis. 9,10 In addition, an intimate relationship between the cutaneous nervous system and melanocytes has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 3,[6][7][8] Furthermore, several studies have shown that extracellular matrix (ECM) proteins, which are responsible for structure formation and the transduction of cellular signalling pathways in the skin, can affect melanogenesis. 9,10 In addition, an intimate relationship between the cutaneous nervous system and melanocytes has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Neighbouring cells around melanocytes, such as keratinocytes, fibroblasts and immune cells, positively or negatively influence melanogenesis by secreting paracrine factors in response to UV irradiation or inflammatory conditions (Fig. ) . Furthermore, several studies have shown that extracellular matrix (ECM) proteins, which are responsible for structure formation and the transduction of cellular signalling pathways in the skin, can affect melanogenesis .…”
mentioning
confidence: 99%
“…41 Similar to the current findings a dose-dependent manner of CKs increase after irradiation of keratinocytes and melanocytes was described earlier by authors from the present group. 42 In the blood cells of Hiroshima 11 survivors, chronically exposed to IR, transcriptional modulations of several CKs were measured, including IL-1β, IL-2, IL-8, IL-10, IL-12β, TNFα/β, and macrophage colony-stimulating factor. In another study, 43 IL-6 and IL-8 were identified in the growth medium of human dermal fibroblasts after exposure to 2 Gy, IL-6 being reported to promote γH2AX foci formation.…”
Section: Discussionmentioning
confidence: 99%
“…Along with these inflammatory cytokines was observed also increase of MMP-9 factor. Thus, presumably, tissue degeneration markers create the conditions for the development of the inflammation and combined with IL-6 and IL-8 affect cellular differentiation and even phenotype (Decean et al, 2013). MMPs in serum and synovial fluid have become valuable diagnostic biomarkers for evaluation of psoriatic arthritis and its treatment with TNF-α blocking agents used also in the treatment of psoriasis (Giannelli et al, 2004;Chandran et al, 2013).…”
Section: Concomitant Determination Of Inflammatory Cytokines Tnf-α Il-1αmentioning
confidence: 99%